MODULAR RATING SYSTEM OF ASSESSMENT STUDENT KNOWLEDGE - A.A. Permyakov; N.I. Zelenkova (Academy of Cognitive and Natural Sciences, 2022)
In Permjakova Alexander Anatoljevicha and Zelenkovoj Natalia Ivanovny's clause theoretical questions of a modul-rating estimation of knowledge ofpupils of modem school are considered.